Do limitations in land rights transferability influence mobility rates in Ethiopia? - de Brauw, Alan; Mueller, Valerie (International Food Policy Research Institute, 2011)
The migration of household members is potentially an attractive pathway out of poverty for many rural households in developing countries. Such households face the challenge of maintaining or improving their livelihoods in the presence of capital market imperfections, vulnerability to climate and macroeconomic shocks, and inaccessibility to credit. For many such households, labor is their main productive asset. Access to opportunities in distant labor markets through migration can increase the earning potential of members of such households (Harris and Todaro 1970). Furthermore, if migration takes place as part of a household decision making strategy, it can help the source household reduce income risks (Stark 1991, Azam and Gubert 2006), at the very least, and potentially improve the well being of the entire household (de Brauw and Harigaya 2007). From the former perspective, households can diversify income risk preemptively by allocating labor spatially to areas where risks to income are not correlated with rural income shocks (Rosenzweig and Stark 1989).